Phonon-Induced Entanglement Dynamics of Two Donor-Based Charge Quantum Bits - Lastra, F (IOP PUBLISHING LTD, 2012)
The entanglement dynamics of a pair of donor-based charge qubits is obtained in an analytical form. The disentanglement is induced by off-resonant scattering of acoustical phonons in the semiconductor host. According to our results, a rather unusual recovery of entanglement occurs that depends on the geometrical configuration of the qubits. In addition, for large times a non-vanishing stationary entanglement is predicted. For the cases of one and two initial excitations, a simple kinetic interpretation allows for an adequate analysis of the observed dynamics. Our results also reveal a direct relation between the disentanglement rate and the inter-donor decoherence rates.